Studi Kopresipitasi Co(II) Menggunakan Kopresipitan Al(OH)3 Secara Spektrofotometri Serapan Atom (SSA) - Monika Yulia; Indang Dewata; Edi Nasra (Jurnal Periodic Jurusan Kimia UNP, 2013)
Has conducted research on the study of coprecipitation Co(II) using copresipitan Al(OH)3 by Atomic Absorption Spectrophotometry. This study aims to find the optimum conditions such as pH coprecipitation, volume of coprecipitan and the volume of nitric acid as eluent and to see efect of Ni(II) to coprecipitation Co(II). Results of analysis using SSA coprecipitation prove that the optimum conditions obtained in a relatively at base pH of the solution that is pH 8, where the condition is colloidal Al(OH)3 formed maximum. At acidic pH colloid formation process is not maximized, while at higher pH colloids formed will dissolve again into tetra hidroksoaluminat ions. Maximum Coprecipitan volume occurs at 12 mL Al3+ 0,2 M, which is the case in vulome maximum absorption of  Co2+ 50 mL 1 ppm by 2,0 mmol colloidal Al(OH)3 while at higher volumes there is a reduction of the metal cation uptake due to competition between the Al metal is more electropositive and have fingers ion is smaller than the cations Co(II). The optimum conditions of volume nitric acid as eluent  occurred on volume of 1 mL with absorption capacity by Al3 was 0.0905 mg / g, where as in the volume of eluent managed to extract maximum metal cations while the volume is higher dilution solution causes a decrease in the concentration of metal cations soluble in the eluent. The addition of nickel metal ions affect coprecipitation of metal kobalt  because cobalt and nickel  is a 3d transition which has a tendency of the same characteristic.